Simple Orthodontic Correction of Rotated Malpositioned Teeth Using Sectional Wire and 2×4 Orthodontic Appliances in Mixed-Dentition: A Report of Two Cases - S. Nagarajan M. P. Sockalingam; Ahmad Shuhud Irfani Zakaria; Khairil Aznan Mohamed Khan; Fayyadhah Mohd Azmi; Nurhidayah Muhd Noor (Case Reports in Dentistry)
The correction of rotated malpositioned tooth/teeth into the dental arch alignment in the mixed-dentition is often a challenging task for paediatric dentists. Failure in addressing this issue can bring about detrimental effect to the developing dentition and increases the probability of a complex orthodontic treatment in later years. Factors such as severity of the malpositioned teeth, patient’s treatment compliance, limitation in specific functions of the selected appliance, availability of bone and space may dictate the success of the treatment. The combined use of a simple sectional orthodontic wire appliance and a 2×4 orthodontic appliance has been shown to produce a positive effect. The appliances resulted in derotation of the rotated malpositioned teeth and bringing them into arch alignment in two cases. This treatment option had eliminated the detrimental effects to the developing dentition and helped patients to enhance their smile and dental aesthetics.